Effects of urban association on the movement ecology of hamadryas baboons (Papio hamadryas) in Saudi Arabia - Zaffar Rais Mir; Paula Pebsworth; Jack Hardman; Saleh Ala’amri; Ali Alahmari; Khalid Almalki; Ahmed Boug (PLoS ONE, 2026)
Human–wildlife conflict involving primates is an emerging conservation concern in rapidly urbanizing regions. The hamadryas baboon ( Papio hamadryas ), the only native non-human primate of the Arabian Peninsula, increasingly exploits anthropogenic food sources, intensifying human–baboon conflict across southwestern Saudi Arabia. To examine how human-modified environments influence baboon spatial ecology; we fitted GPS collars to ten adult males representing groups that are regarded as living in urban, natural and semi-natural environments across five regions. Over nine months, we collected 13,962 location fixes and analyzed them using empirical variograms, home range analysis, and minimum daily path length estimates. Variogram analyses indicated that baboons living in a natural environment exhibited the greatest space-use extent, semi-natural individuals showed intermediate and more variable space-use dynamics, whereas baboons living in urban areas displayed restricted movement. Hamadryas baboons living in natural environments exhibited the largest home ranges with a median of 8.79 km 2 (range: 6.19–13.86 km 2 ) and minimum daily path lengths with median 3.33 km (range 0.02–20.6 km), whereas baboons living in urban areas maintained the smallest ranges with a median of 1.31 km 2 (range: 1.24–1.79 km 2 ) and the minimum daily path lengths with a median of 2.16 km (range: 0.01–4.85 km). The proportion of daytime spent in urban areas increased along the gradient, 7.2% (natural), 40.6% (semi-natural), and 55.0% (urban). These findings support the Resource Dispersion Hypothesis, suggesting that food predictability shapes baboon space use more than resource scarcity. The study strengthens ongoing conflict-mitigation efforts by providing insights into baboon movement patterns and supporting the ecological differentiation of natural, semi-natural, and urban baboon groups, thereby informing category-specific management interventions.